Effect and Mechanism of Running on Mouse Emphysema Model Induced by Cigarette Extract - LI Yongrong; XIE Haibin; LI hong; SUN Jie (康复学报)
ObjectiveTo observe the effect of running on mouse emphysema model induced by cigarette extract, and to explore its mechanism based on signal transducer and activator of transcription 3 (STAT3).MethodsA total of 40 male C57BL/6 mice were randomly divided into control group, exercise group, emphysema group and emphysema + exercise group, with 10 mice in each group. The control group and the exercise group were intraperitoneally injected with 0.3 mL phosphate buffer saline (PBS) at the 0, 11th and 22th day in the experiment; the emphysema group and the emphysema + exercise group were intraperitoneally injected with 0.3 mL cigarette extract at the 0, 11th and 22th day in the experiment. The control group and the emphysema group were free to move in the cage from the 23rd to 29th day; the exercise group and the emphysema + exercise group received aerobic running training from the 23rd day to the 29th day (15 m/min, 30 minutes a day). Hematoxylin eosin (HE) staining was used to observe the pathological changes of lung tissue and evaluate the severity of emphysema in the four groups; the expression levels of inflammatory cells and cytokines in bronchoalveolar lavage fluid (BAL) and serum were analyzed to evaluate the pulmonary and systemic inflammation of the four groups; Western blot method was used to analyze the expression of STAT3 in lung tissues.Results1) Severity of emphysema: compared with the control group, the alveolar chord length of mice in the emphysema group and the emphysema + exercise group significantly increased, the difference was statistically significant (P<0.05). Compared with the emphysema group, the alveolar chord length in the emphysema + exercise group significantly decreased，the difference was statistically significant (P<0.05). 2) Lung inflammation: compared with the control group, the contents of white blood cells, neutrophils and lymphocytes and the expression levels of IL-1β, IL-6, and IL-17 in BAL of the emphysema group and the emphysema + exercise group significantly increased, while the IL-10 level significantly decreased (P<0.05). Compared with the emphysema group, the counts of white blood cells, neutrophils and lymphocytes and the expression levels of IL-1β, IL-6, and IL-17 in BAL of the emphysema + exercise group were statistically lower, and the IL-10 level was statistically higher, the difference was statistically significant (P<0.05). 3) Systemic inflammation: compared with the control group, the counts of white blood cells, neutrophils and lymphocytes in the emphysema group statistically increased (P<0.05), the expression levels of IL-1β, IL-17, and TNF-α in the emphysema group and the emphysema + exercise group statistically increased, and the IL-10 level statistically decreased (P<0.05). Compared with emphysema group, the counts of white blood cells, neutrophils and lymphocytes and the expression levels of IL-1β, IL-17, and TNF-α in the emphysema + exercise group were lower, and the IL-10 level was statistically higher, the difference was statistically significant (P<0.05). 4) STAT3 expression level in lung tissues: compared with the control group, p-STAT3 expression level in lung tissues of the emphysema group and the emphysema + exercise group statistically increased (P<0.05). Compared with the emphysema group, the expression level of p-STAT3 in lung tissues of the emphysema + exercise group statistically decreased , the difference was statistically significant (P<0.05).ConclusionRunning could reduce the pulmonary and systemic inflammation, and alleviate the pathological manifestations of emphysema in the mice model of emphysema, and its mechanism may be related to the inhibition of STAT 3 activation.